The Efect of Knowledge Management on Employee Performance With Organizational Culture as a Moderation Variable at PT. PLN UP3 Makassar Utara - Muh. Ilham Nur; Muh. Idrus Taba; Wardhani Hakim (Lafadz Jaya Publisher, 2023)
The purpose of this study is to determine the influence of knowledge management on employee performance with organizational culture as a moderation variable in PT. PLN UP3 Makassar Utara. This research uses a quantitative approach. The population in this study was all employes of PT. PLN UP3 Makassar Utara which amounted to 72 people with a total sample of 39 people. The technique used in data collection is a survey method in the form of a questionnaire which will then be processed in the SPSS application. The results showed that knowledge management had a significant positive effect on the performance of PT. PLN UP3 Makassar Utara, as well as organizational culture moderate the influence of knowledge management on the performance of PT. PLN UP3 Makassar Utara.